IMPLEMENTATION OF GUIDANCE FOR RECIDIVIST INMATES OF NARCOTICS CRIMES AT THE KEDUNGPANE CORRECTIONAL INSTITUTION - Olga Loveano Revorma; Mujiono Hafidh Prasetyo (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
LAPAS is a place to improve the quality of prison inmates so that they are aware of their mistakes, improve themselves, and do not repeat crimes so that they can integrate well into the community. Not a few prisoners who, after completing their prison term, repeat their crimes (recidivists). This study aims to determine the current policy of formulating a coaching system for recidivist convicts of narcotics crime; how to carry out coaching for recidivist convicts of narcotics abuse in Class I prisons in Semarang. Based on the results of the study, it can be seen that in the practice of implementing guidance at the Class I prison in Semarang for narcotics abuse recidivists, applying the security aspect (security approach), while regarding the coaching program there is no difference from other inmates. Guidance at the Class I prison in Semarang aims to enable prisoners to become fully human as has become the direction of national development. Correctional inmates in obtaining guidance are adjusted to the principles contained in Pancasila, the 1945 Constitution of the Republic of Indonesia, and the Minimum Standard Rules (SMR). The guidance and guidance of recidivist convicts of narcotics abuse carried out in Class I prisons in Semarang based on the Decree of the Minister of Justice of the Republic of Indonesia No. M. In 2019, the Class I prison in Semarang handling narcotics abuse prisoners carried out a rehabilitation program using the therapeutic community method..